2011
DOI: 10.1016/j.ejcts.2011.01.087
|View full text |Cite
|
Sign up to set email alerts
|

Post-cardiotomy extracorporeal cardiopulmonary resuscitation in neonates with complex single ventricle: analysis of outcomes

Abstract: ECMO support in neonates with FSV requiring ECPR can result in favorable outcome in more than half of patients at hospital discharge. Aggressive strategy toward timely application of ECPR is justified. Expeditious ECPR deployment after proper patients' selection, refinement of CPR quality and use of adjunctive neuroprotective interventions, such as induced hypothermia, might further improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 23 publications
6
64
0
Order By: Relevance
“…However, duration of CPR was identified as is a strong predictor of survival in a recent large, singlecenter study (15 min survivors vs. 40 min non-survivors, P=0.009), in which children who required ≥30 min of CPR had 79% reduced odds of hospital survival (24). Several single-center published reports do not identify duration of CPR as a predictor of ECPR survival but the difference in median duration of CPR between survivors and nonsurvivors was generally small (<5 min) (25)(26)(27). In contrast, pre-ECLS resuscitation >30 minutes has been identified as a significant independent risk factor of mortality in adults who experience out-of-hospital cardiac arrest (28).…”
Section: Duration Of Pre-ecpr Resuscitationmentioning
confidence: 99%
“…However, duration of CPR was identified as is a strong predictor of survival in a recent large, singlecenter study (15 min survivors vs. 40 min non-survivors, P=0.009), in which children who required ≥30 min of CPR had 79% reduced odds of hospital survival (24). Several single-center published reports do not identify duration of CPR as a predictor of ECPR survival but the difference in median duration of CPR between survivors and nonsurvivors was generally small (<5 min) (25)(26)(27). In contrast, pre-ECLS resuscitation >30 minutes has been identified as a significant independent risk factor of mortality in adults who experience out-of-hospital cardiac arrest (28).…”
Section: Duration Of Pre-ecpr Resuscitationmentioning
confidence: 99%
“…Several pediatric studies have shown increased mortality rates for patients cannulated after 30 minutes of conventional CPR. 7,11,28,34 However, other retrospective studies [8][9][10]12,20,26,27,29,31,32 of pediatric patients have shown positive outcomes with median CPR duration of 30 to 50 minutes. Even more interesting are the multiple case reports 24,27,30,32,37 of successful cannulation and survival to discharge in patients receiving CPR of up to 90 to 220 minutes.…”
Section: Population Of Patientsmentioning
confidence: 96%
“…Morris et al 32 Paden et al 2 Polimenakos et al 26 Prodhan et al 27 Raymond et al 8 Shah et al 33 Sivarajan et al 34 Thiagarajan et al 6 Tajik and Cardarelli 7 Wolf et al 24 Thourani et al 25 630 (40) 8 (57) 24 (72) 87 (44) 9 (33) 14 (38) 261 (38) 114 ( survive after treatment with ECPR. 8 Few published data support preexisting measurements as indicators for survival.…”
Section: Referencementioning
confidence: 99%
See 1 more Smart Citation
“…1 Despite huge advances in ECMO hardware technology, intensive care unit (ICU) management, and more judicious indications to deploy ECMO, weaning from cardiac ECMO after congenital heart surgery or after rapid resuscitation for acute cardiac failure of any origin still ranges only between 56% and 79%. [2][3][4][5][6] Survival to hospital discharge is unfortunately even lower, ranging between 38% and 59%. [2][3][4][5][6][7] While increasingly precise protocols are being developed to guide ECMO management, it is still difficult to predict, in the first days after ECMO implantation, whether cardiac recovery is likely or not.…”
Section: Introductionmentioning
confidence: 99%